Synthesis and Bioactivity Characterization of Scutellarein Sulfonated Derivative - Ting Gu (Molecules, 2017)
Scutellarin (1) has been widely used to treat acute cerebral infarction in clinic, but poor aqueous solubility decreases its bioavailability. Interestingly, scutellarin (1) could be metabolized into scutellarein (2) in vivo. In this study, a sulfonic group was introduced at position C-8 of scutellarein (2) to enhance the aqueous solubility of the obtained derivative (3). DPPH (1,1-diphenyl-2-picrylhydrazyl)-radical scavenging ability and antithrombic activity were also conducted to determine its bioactivity. The result showed that scutellarein derivate (3) could be a better agent for ischemic cerebrovascular disease treatment.